2016
DOI: 10.1111/jfpp.12704
|View full text |Cite
|
Sign up to set email alerts
|

The Monitoring, Via an In vitro Digestion System, of the Bioactive Content of Vegetable Juice Fermented with Saccharomyces cerevisiae and Saccharomyces boulardii

Abstract: In the present study, an in vitro model simulating gastro-intestinal (GI) digestion, was adapted to assess phenolic compounds from watermelon radish (R), red beet (RB) and black carrot (RC) juices fermented using Saccharomyces cerevisiae and Saccharomyces boulardii. The phenolic profiles were analyzed by high pressure liquid chromatography (HPLC) analyses. The total phenolic content, the antioxidant capacity and viability of microbiota was investigated in terms of bioaccessibility, and sensorial evaluation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 78 publications
2
16
0
Order By: Relevance
“…Saccharomyces boulardii influences the synthesis of active phytochemicals such as isoflavones (Rekha and Vijayalakshmi ), and phenols (Değirmencioğlu et al . ), thus increasing the antioxidant capacity of the products. Additionally, its utilization enhances bioavailability of essential minerals and B‐vitamins (Chandrasekar‐Rajendran et al .…”
Section: Nutritional and Nutraceutical Implications Of S Boulardii Imentioning
confidence: 99%
See 3 more Smart Citations
“…Saccharomyces boulardii influences the synthesis of active phytochemicals such as isoflavones (Rekha and Vijayalakshmi ), and phenols (Değirmencioğlu et al . ), thus increasing the antioxidant capacity of the products. Additionally, its utilization enhances bioavailability of essential minerals and B‐vitamins (Chandrasekar‐Rajendran et al .…”
Section: Nutritional and Nutraceutical Implications Of S Boulardii Imentioning
confidence: 99%
“…A study carried out by Değirmencioğlu et al . (), concluded that vegetable juices (radish, carrots and beets) fermented with S. cereviseae and S. boulardii were rich in phenols and exerted high antioxidant capacity. Particularly, that beet juice had the greatest bio accessibility and antioxidant activity.…”
Section: Nutritional and Nutraceutical Implications Of S Boulardii Imentioning
confidence: 99%
See 2 more Smart Citations
“…In agreement with our data, Henning et al (2014) reported a 21.5% and 8.1% decrement of TEAC (trolox equivalent antioxidant capacity) in green tea and grape seed samples during in vitro simulated digestion. In another study, Değirmencioğlu et al (2016) concluded DPPH bioaccessibilities of fermented vegetable juices between 16-32%. In spite of the fact that polyphenols supply major antioxidant potency of the samples, our results displayed that digestion may alter antioxidant properties depending on the variations in polyphenol content (Henning et al, 2014).…”
Section: Antioxidant Capacitymentioning
confidence: 99%